Corazonin Signaling Is Required in the Male for Sperm Transfer in the Oriental Fruit Fly Bactrocera dorsalis - Hou, Qiu-Li; Chen, Er-Hu; Jiang, Hong-Bo; Yu, Shuai-Feng; Yang, Pei-Jin; Liu, Xiao-Qiang; Park, Yoonseong; Wang, Jin-Jun; Smagghe, Guy (Frontiers in Physiology, 2018)
Corazonin (Crz) is a widely distributed neuropeptide (or neurohormone) in insects with diverse physiological functions. The present study aimed to reveal the functions of Crz and its receptor (CrzR) in the regulation of sexual behavior and fertility in male B. dorsalis. Tissue-specific expression analyses showed that the BdCrz transcript was most abundant in the central nervous system (CNS), and the BdCrzR transcript was most abundant in both the fat body and CNS. Immunochemical localization confirmed that three pairs of Crz-immunoreactive neurons are located in the dorso-lateral protocerebrum region of male adult brain. Importantly, RNAi-mediated Crz knockdown lengthened mating duration in males, and knockdown of Crz or CrzR strongly decreased male fertility in the following three days, while the courtship behavior and mating efficiency were not affected. The reduced number of sperm in the reproductive organs of mated females indicated that Crz knockdown in males reduced sperm transfer. The findings of this study indicate that Crz contributes to the reproductive physiology of the oriental fruit fly B. dorsalis by regulating sperm transfer in male adults.